Developmental Trajectories of Letter and Speech Sound Integration During Reading Acquisition - Karipidis, Iliana I.; Pleisch, Georgette; Di Pietro, Sarah V.; Fraga-González, Gorka; Brem, Silvia (Frontiers in Psychology, 2021)
Reading acquisition in alphabetic languages starts with learning the associations between speech sounds and letters. This learning process is related to crucial developmental changes of brain regions that serve visual, auditory, multisensory integration, and higher cognitive processes. Here, we studied the development of audiovisual processing and integration of letter-speech sound pairs with an audiovisual target detection functional MRI paradigm. Using a longitudinal approach, we tested children with varying reading outcomes before the start of reading acquisition (T1, 6.5 yo), in first grade (T2, 7.5 yo), and in second grade (T3, 8.5 yo). Early audiovisual integration effects were characterized by higher activation for incongruent than congruent letter-speech sound pairs in the inferior frontal gyrus and ventral occipitotemporal cortex. Audiovisual processing in the left superior temporal gyrus significantly increased from the prereading (T1) to early reading stages (T2, T3). Region of interest analyses revealed that activation in left superior temporal gyrus (STG), inferior frontal gyrus and ventral occipitotemporal cortex increased in children with typical reading fluency skills, while poor readers did not show the same development in these regions. The incongruency effect bilaterally in parts of the STG and insular cortex at T1 was significantly associated with reading fluency skills at T3. These findings provide new insights into the development of the brain circuitry involved in audiovisual processing of letters, the building blocks of words, and reveal early markers of audiovisual integration that may be predictive of reading outcomes.